2015
DOI: 10.1590/1807-1929/agriambi.v19n3p286-292
|View full text |Cite
|
Sign up to set email alerts
|

Determinação das propriedades geométricas, físicas e mecânicas do sistema fruto-pedúnculo-ramo do cafeeiro

Abstract: R E S U M OO método de elementos finitos tem sido empregado no projeto de máquinas e para o estudo do comportamento dinâmico do cafeeiro. Objetivou-se, neste trabalho, determinar as propriedades geométricas, físicas e mecânicas do sistema fruto-pedúnculo-ramo do cafeeiro. As dimensões foram determinadas por meio de processamento de imagens, as massas e os volumes mensurados utilizando-se balança e proveta, respectivamente. Os módulos de elasticidade foram determinados por meio de ensaios mecânicos de compressã… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 15 publications
3
27
0
2
Order By: Relevance
“…Damping ratios obtained confirm that the fruit-rachilla system is under-damped given that the average values were always below one (Table 3), as determined by COELHO et al (2015) for coffee plant branch stems.…”
Section: Villar Et Alsupporting
confidence: 63%
See 1 more Smart Citation
“…Damping ratios obtained confirm that the fruit-rachilla system is under-damped given that the average values were always below one (Table 3), as determined by COELHO et al (2015) for coffee plant branch stems.…”
Section: Villar Et Alsupporting
confidence: 63%
“…For soya, RIBEIRO et al (2007) reported values for the modulus of elasticity, analyzing different axes, to be between 10.2 and 23.1MPa for moist grains. In a study on coffee stalks, using green fruit, COELHO et al (2015) reported a modulus of elasticity of 3.91MPa.…”
Section: Villar Et Almentioning
confidence: 99%
“…Several factors influence vibration harvest, such as the shape, size, structure and maturity stage of fruits, as well as frequency and amplitude of vibration (Ferraz et al 2012, Coelho et al 2015, Santos et al 2015, Ferreira Junior et al 2016.…”
Section: Abstract Resumomentioning
confidence: 99%
“…These properties are specific for each species and product and can be influenced by the environment, during its formation and development (Costa et al 2014, Coelho et al 2015, Villar et al 2017.…”
Section: Abstract Resumomentioning
confidence: 99%
“…Models of the fruit-stem and branch geometries ( Figure 3) were generated using the Solid Works 2011 CAD software and were based on dimensions determined experimentally by Coelho, Santos, Pinto, and Queiroz (2015) ( Table 3, 4 and 5). Figure 3.…”
Section: Experimental Determination Of Natural Frequenciesmentioning
confidence: 99%